Metal-organic frameworks-derived catalysts for contaminant degradation in persulfate-based advanced oxidation processes. (15th November 2022) - Wang, Luyao; Luo, Dan; Yang, Jiapeng; Wang, Chongqing
Abstract: Effective treatment of emerging organic contaminants (EOCs) is a key concern for human beings. Advanced oxidation processes (AOPs) have become one of the core techniques of EOCs removal because of the high oxidation efficiency, complete mineralization, and controllable process. Sulfate radicals-based AOPs overcome the shortcomings of conventional Fenton processes. The development of efficient catalysts is major limitation of sulfate radicals-based AOPs for EOCs removal from wastewater. Metal organic framework (MOFs) receives growing global attention due to excellent properties of large surface area, flexible synthesis methods, and modifiable structure. Numerous researches have been conducted to fabricate MOFs-based catalysts. Herein, studies on MOFs-based materials as catalysts for catalytic removal of EOCs were summarized. The synthesis methods of MOFs were briefly described. Researches on MOFs materials as persulfate activators were reviewed from the perspective of Fenton-like and photo-Fenton system. Additionally, the effects of process factors including catalyst dosage, persulfate concentration, solution pH, coexisting inorganic anions, natural organic matter, and temperature on the catalytic efficiency were systematically summarized. Finally, the stability and toxicity of MOFs-based catalysts that affect the practical application was discussed. This work provides better understanding of sulfate radicals-based AOPs using MOFs-based catalysts for EOCs removal. Graphical abstract: Image 1 Highlights: MOFs-based catalysts are promising for EOCs removal via sulfate radicals-based AOPs. MOFs-based catalysts for removing EOCs are summarized in Fenton-like, photo-Fenton and electro-Fenton system. Effects of various process factors on the catalytic efficiency were systematically discussed. This work provides insights into catalyst design, catalytic mechanism, and process optimization.